2016
DOI: 10.1039/c6ra07486c
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentals of chemical incorporation of ionic monomers onto polymer colloids: paving the way for surfactant-free waterborne dispersions

Abstract: In this article, the fundamentals of the chemical incorporation of a pH and temperature insensitive ionic monomer (sodium styrene sulfonate, NaSS) onto the polymer particles was investigated in an attempt to go beyond the current technology for production of waterborne polymer dispersion, which is based on the use of surfactants to stabilize the dispersion. The success of this approach requires to chemically incorporate the NaSS onto the polymer particles minimizing at the same time the amount of water soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In all polymerizations a ratio of 2:3 was maintained between GMA and SSS respectively. The comonomer SSS is a reactive surfactant . Gelation of polymerization reaction mixtures occurred within an hour and the reaction was continued for additional 3 h by which time stirring of reaction mixture stopped.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all polymerizations a ratio of 2:3 was maintained between GMA and SSS respectively. The comonomer SSS is a reactive surfactant . Gelation of polymerization reaction mixtures occurred within an hour and the reaction was continued for additional 3 h by which time stirring of reaction mixture stopped.…”
Section: Resultsmentioning
confidence: 99%
“…SSS can function as reactive surfactant in the copolymerization. SSS has been used for making surfactant free copolymers with common vinyl monomers for making high solid content polymer dispersions . Sulfonates are also well‐known anionic surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…In our approach, single ion nanoparticles were obtained in the form of a colloidal dispersion in water, commonly defined as latex, adapting a semi-batch emulsion polymerization strategy reported in detail elsewhere. [19][20][21] Briefly, the reactor was initially charged with water purged with a gentle flow of N2 and heated to 80ºC. Three streams were injected to the reactor: one containing the main monomer (methyl methacrylate, MMA)…”
Section: Synthesis Of Lithium Sulfonamide Functional Poly(methyl Methacrylate) Nanoparticlesmentioning
confidence: 99%
“…Surprisingly, much less attention has been paid to the use of functionalized polymeric nanoparticles despite polymers offer a wide range of easily up-scalable techniques. [17][18][19][20][21] For instance, emulsion polymerization, the more versatile polymerization technique to produce waterborne polymer dispersions, offers a straight-forward and industrially feasible method to obtain polymer nanoparticles of a variety of compositions and with controllable and monodispersed sizes between 50 and 500 nm. 22,23 Recently, Kim et al 24 reported the synthesis of ionic functional polymer nanoparticles by post-functionalization strategies of polymer particles which, as indicated before, is most straightforward option to mass production.…”
Section: Introductionmentioning
confidence: 99%
“…This is challenging as NaSS is completely water-soluble and its concentration in the organic phase is virtually zero. Investigation of the fundamentals of chemical incorporation of ionic monomers in polymer colloids [22] paved the way towards the synthesis of surfactant-free waterborne polymer dispersions under industrial-like semicontinuous conditions with solids contents in the upper range of commercial latexes (from 50 wt% to 64 wt%). A modest concentration of NaSS (1.35 wt% based on monomers) was used and a high incorporation of NaSS (83.5%) was achieved [23,24].…”
Section: Introductionmentioning
confidence: 99%